2011
DOI: 10.1158/0008-5472.can-10-3776
|View full text |Cite
|
Sign up to set email alerts
|

MYC and Metastasis

Abstract: Aggressive primary tumors express transcriptional signatures that correlate with their metastatic propensity. A number of these signatures have been deployed in the clinic as risk stratification tools. However, the molecular basis of these clinically useful prognostic signatures has remained a largely unresolved area of controversy. We recently found that many prognostic signatures reflect the activity of the MYC oncogene, which in turn regulates tumor metastasis through specific effects on cancer cell invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 39 publications
5
123
0
1
Order By: Relevance
“…The oncogene c-Myc enhances protein translation through transactivating diverse targets, such as initiation factors, ribosomal proteins, and rRNAs. Activation of c-Myc is found in a variety of cancers, including breast cancer, and its activation seems to be a surrogate marker for cancers (44)(45)(46)(47)(48)(49). The role of c-Myc in driving protein synthesis is in part attributed to promoting ribosome production through transcribing a number of ribosomal proteins (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogene c-Myc enhances protein translation through transactivating diverse targets, such as initiation factors, ribosomal proteins, and rRNAs. Activation of c-Myc is found in a variety of cancers, including breast cancer, and its activation seems to be a surrogate marker for cancers (44)(45)(46)(47)(48)(49). The role of c-Myc in driving protein synthesis is in part attributed to promoting ribosome production through transcribing a number of ribosomal proteins (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The c-Myc transcription factor is one of the most important somatically mutated oncogenes in human cancer and confers a selective advantage to cancer cells by promoting protein synthesis, proliferation, cell survival, differentiation, genetic instability, angiogenesis, hypoxia-mediated cancer progression, and metastasis (33,33,47,(62)(63)(64)(65)(66). Studies have shown that c-Myc up-regulates both eIF4E and eIF4G gene expression (58).…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51][52][53][54][55] Both OSM/STAT3-and TGFb-induced senescence require the repression of MYC. 40,[56][57][58][59] Our lab has previously demonstrated that the expression of MYC from a constitutive promoter prevents OSM-or RAS-induced senescence and alters the response of HMEC to persistent oncogenic stimuli, from growth suppressive to growth promoting.…”
Section: Persistent Osm/stat3 Signaling Promotes Smad Targetgene Tranmentioning
confidence: 99%